The Ratio of Activity and Profitability to Capital Structure of Mining Companies on the Indonesia Stock Exchange - Vicky Rosalia; Yusnaini (International Journal of Economics (IJEC), 2022)
The purpose of this study was to examine the effect of the Activity Ratio as measured by Total Asset Turn Over (TATO) and Profitability as measured by Sales Growth on Capital Structure as measured by the Debt to Equity Ratio. This type of research is causality research. The population in this study used 58 Mining Sector companies listed on the Indonesia Stock Exchange during the 2018-2020 period using a purposive sampling technique to obtain a sample of 49 companies whose observation period was 3 years with a total of 147 data observations. Testing research data using panel data regression analysis. The results showed that the Activity Ratio (TATO) partially had a positive and significant effect on Capital Structure (DER). Meanwhile, the Profitability Ratio (SG) partially has no significant effect on Capital Structure (DER) in Mining Sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period.